Parenting by lying and children's lying to parents: the moderating role of children's beliefs - Low, Petrina Hui Xian (2024)
How are children socialized about lying? One way is parental modeling of lying given that parents tell various lies to their children for parenting purposes, which is a practice known as parenting by lying. Importantly, how children perceive and interpret the lying behavior around them may be crucial to how they then learn to lie. Yet, we do not know how children's perceptions of different types of parental lies drive this socialization. In a comprehensive birth cohort of parent-child dyads (N = 564; children aged 11 and 12 years) in Singapore, we collected multi-informant reports of instrumental lies (parental lies told for child compliance) and white lies (parental lies told to instill positive emotions), children's belief in parental lies, and children's lying to parents. We found greater consistency in parent and child reports of instrumental lies than of white lies and that children reported greater belief in instrumental lies than in white lies. Children's reported exposure to instrumental lies was associated with greater lying to parents. However, for white lies this relationship was evident only when children had moderate to low beliefs in parental lies. Examining the interplay between parental lies and children's beliefs in those lies, the current study illuminates the potential pathways to children's lying behaviors.